Pes varus correction in dachshunds with mini hybrid external skeletal fixators. Issue 4 (14th December 2021) - Chau, L; Wilson, L
Abstract : Aim: To evaluate the clinical and radiographic outcome of pes varus deformity correction in dachshunds managed with acute medial opening wedge osteotomy of the distal tibia and stabilised with a mini hybrid external skeletal fixator (HESF). Methods: Surgical correction involved a transverse osteotomy over the premeasured location at the distal tibia and application of a IMEX mini HESF. All corrections were evaluated using centre of rotation and angulation methodology. Results: Medical records and radiographies of 20 dachshunds (28 pes varus corrections) were reviewed. All osteotomies healed and fixators were removed between 6 and 12 weeks. Lameness resolved in 18 dachshunds (90%) and significantly improved in two dachshunds (10%). Lateral patella luxation (LPL) was detected in 11/28 (39.2%) of the involved pelvic limbs, all of which resolved following pes varus correction. Mean frontal plane alignment (FPA) of the normal and abnormal tibiae were 12.3° valgus (range: 4°–18°) and 25° Varus (range: 16°–41°) respectively. Angular correction ranged between 30° and 50° (Mean: 39°) and the mean post‐operative FPA was 13° valgus (range: 5°–21°). Clinical significance: Pes varus deformity in dachshunds can be corrected by medial opening wedge osteotomy of the distal tibia stabilised by HESF. Single‐session bilateral pes varus corrections can also be performed with minimal morbidity. LPL was commonly detected in dogs with pes varus deformity and all resolved spontaneously following pes varus correction alone.